Brain Plasticity in Charcot-Marie-Tooth Type 1A Patients? A Combined Structural and Diffusion MRI Study - Pontillo, Giuseppe; Dubbioso, Raffaele; Cocozza, Sirio; Tozza, Stefano; Severi, Daniele; Iodice, Rosa; Tedeschi, Enrico; Elefante, Andrea; Brunetti, Arturo; Manganelli, Fiore; Quarantelli, Mario (Frontiers in Neurology, 2020)
Central nervous system involvement has been described in peripheral neuropathies, including different forms of Charcot-Marie-Tooth (CMT) disease. Aim of our study was to systematically investigate possible brain structural modifications in CMT1A patients, using volumetric MRI and diffusion tensor imaging (DTI). In this prospective cross-sectional study, from May-2017 to May-2019, we acquired 3T MRI brain scans of genetically confirmed CMT1A patients and age- and sex-comparable healthy controls. Patients also underwent clinical and electrophysiological examinations assessing motor and sensory domains. Voxel-based morphometry (VBM) and tract-based spatial statistics (TBSS) analyses were performed using a nonparametric approach based on permutations, including age and sex (and total intracranial volume for VBM) as nuisance covariates. When between-group differences emerged at VBM or TBSS analyses, the first eigenvariate was extracted from the cluster and its age- and sex-adjusted standardized residuals tested for correlation with clinical and electrophysiological variables. 20 CMT1A patients (34.5±11.1years; M/F:11/9) were enrolled, along with 20 healthy controls (30.1±10.2years; M/F:11/9). The VBM analysis revealed clusters of significantly increased GM volume in CMT1A patients compared to healthy controls, encompassing the bilateral cerebellar lobules III-VI and the left hippocampus (all ps=0.04), with no differences in terms of DTI metrics at the TBSS analysis. A negative correlation (r=-0.502, p=0.03) emerged between ulnar compound motor action potential and the z-scores corresponding to the right cerebellar cluster of augmented GM volume. Our data show evidence of structural reorganization in the brain of CMT1A patients, possibly reflecting neural plasticity mechanisms in response to peripheral nerve pathology and modulating the effect of axonal degeneration on functional impairment.